Cytokeratins 8 and 19 in the Mouse Placental Development - Tamai, Yoshitaka (The Rockefeller University Press, 2000)
To investigate the expression and biological roles of cytokeratin 19 (K19) in development and in adult tissues, we inactivated the mouse K19 gene (Krt1-19) by inserting a bacterial β-galactosidase gene (lacZ) by homologous recombination in embryonic stem cells, and established germ line mutant mice. Both heterozygous and homozygous mutant mice were viable, fertile, and appeared normal. By 7.5–8.0 days post coitum (dpc), heterozygous mutant embryos expressed lacZ in the notochordal plate and hindgut diverticulum, reflecting the fact that the notochord and the gut endoderm are derived from the axial mesoderm-originated cells. In the adult mutant, lacZ was expressed mainly in epithelial tissues. To investigate the possible functional cooperation and synergy between K19 and K8, we then constructed compound homozygous mutants, whose embryos died ∼10 dpc. The lethality resulted from defects in the placenta where both K19 and K8 are normally expressed. As early as 9.5 dpc, the compound mutant placenta had an excessive number of giant trophoblasts, but lacked proper labyrinthine trophoblast or spongiotrophoblast development, which apparently caused flooding of the maternal blood into the embryonic placenta. These results indicate that K19 and K8 cooperate in ensuring the normal development of placental tissues.